Oil extraction imperils Africa's Great Lakes - Verheyen, Erik; Abila, R.; Akoll, P.; Albertson, C.; Antunes, D.; Banda, T.; Bills, R.; Bulirani, A.; Manda, A. Chocha; Cohen, A. S.; Cunha-Saraiva, F.; Derycke, S.; et al. (American Association for the Advancement of Science, 2016)
The article points out the intent of several African countries to extract oil in the East African Great Lakes region including all the consequences. The authors list the grave risks of a potential accident and problems with its recovery under difficult local circumstances, and summarize how the oil spills would affect the health, water supply and food security of local communities including a catastrophic impact on biodiversity of these fragile ecosystems.
Keywords: Tanganyika, Malawi, Victoria Lake, water resources, exploitation of hydrocarbons